(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research work was carried out to study the various causes which lead the assets of banks to become non-performing assets. In India, major part of loans and advances is provided by banks to the farmers, industrialist and households. Indian agriculture sector depends on natural climates like rain, flood etc. and success of industrial sector depends mainly on business environment or on market sentiments. Therefore, many times industrialists, farmers and households are not found in capacity of repayment of their loan’s installment and interest thereon and these loans and advances by banks become NPA for them. In this paper, the researcher tries to out the main causes of NPA. To get answers for the research questions, data were collected from primary sources through schedule instrument and collected data were analysed with the help of percentage analysis.